Cybersecurity and Crisis Leadership: A Contemporary Theoretical Expansion - Nowduri, Srinivas; Amba, Sekhar (Archives of Business Research, 2025)
Cyber incidents have evolved from isolated technical breaches into complex organizational crises that demand resilient, adaptive leadership. This paper reconceptualizes cybersecurity leadership as a specialized extension of crisis leadership, grounded in interdisciplinary theory spanning crisis management, digital transformation, high reliability organizing, and cyber resilience. It introduces two integrated models—the Cyber Crisis Lifecycle and the Cyber Leadership Hexagon—to articulate leadership roles across the incident continuum and define six core competencies: technical literacy, ethical judgment, digital sensemaking, stakeholder coordination, agility under threat, and resilience orientation. These models provide a comprehensive framework for understanding cyber leadership in environments marked by persistent ambiguity, socio-technical complexity, and adversarial threat. This theoretical expansion contributes to the emerging literature on digital-era leadership and lays a foundation for future empirical validation and cross-cultural application.